Perancangan Sistem Informasi Inventory Barang (E-Gudang) Usaha Mikro Pada CV. Nonnetedy Berbasis Web - Arizki, Kiki; Tisnawati, Rini (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The lack of accurate information regarding the stock of goods in a warehouse makes information biased regarding the availability of goods. Information systems are growing rapidly following the advancement of technology. Therefore we need a system that becomes the information center in a warehouse. The goods inventory system is a system that focuses on processing data related to goods in the warehouse. Observations made in the company CV. NONNETEDY using the system development method used by the researcher is Waterfall. The process in development used is UML (Unified Modeling Language) using the PHP programming language and MySql database. The result of implementing an inventory system that researchers use to manage goods data, starting from systematically distributing goods in and out. This makes it easier for users or companies to print reports and have accurate results on the report